2006
DOI: 10.1590/s0101-20612006000100033
|View full text |Cite
|
Sign up to set email alerts
|

Atitude do consumidor frente à irradiação de alimentos

Abstract: O mérito da irradiação está em sua capacidade de destruir microorganismos patogênicos e deteriorantes presentes nos alimentos. É empregada, ainda, para eliminar insetos e retardar o processo germinativo em produtos vegetais. Desta forma, há um aumento na segurança dos alimentos destinados ao consumo humano e uma redução nas perdas causadas por deterioração [6]. A irradiação é um processo físico que vem sendo estudado há vários anos, tendo o seu emprego regulamentado pelo Food and Drug Adminstration (FDA) desde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
30

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 2 publications
1
28
0
30
Order By: Relevance
“…Application of radiation has also been guided by Good Manufacturing Practices (GMP's) (LAGUNAS-SOLAR, 1995). By the 1980s and 1990s, new regulations emerged with the aim of extending this technology to other foods (ORNELLAS et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Application of radiation has also been guided by Good Manufacturing Practices (GMP's) (LAGUNAS-SOLAR, 1995). By the 1980s and 1990s, new regulations emerged with the aim of extending this technology to other foods (ORNELLAS et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…International organizations such as the Food and Agriculture Organization (FAO) and World Health Organization (WHO) has been reviewed all researches about this theme and concluded that irradiated food is safe and beneficial (Ornellas;Gonçalves;Martins, 2006). Similarly, the nutritional value of irradiated foods was compared with other food processing methods, with favorable results showing that the irradiation uses are the same with common treatments or better.…”
Section: Food Irradiationmentioning
confidence: 99%
“…Na verdade, não são limitações de natureza técnica ou científica, mas relacionadas ao custo de sua utilização e de aceitação pelo consumidor (Ornellas et al, 2006).…”
Section: -Aceitação De Alimentos Irradiadosunclassified
“…O uso comercial também cresce lentamente devido a interpretações equivocadas por grande parte dos consumidores brasileiros, que possuem uma ideia preconcebida, que pode estar relacionada com a imagem negativa que a energia nuclear deixou ao mundo após as bombas atômicas de Hiroshima e Nagasaki, na Segunda Guerra Mundial, o acidente nuclear de Chernobyl e, especificamente no Brasil, o desastre com o Césio 137, em Goiânia, e ainda devido à interpretação errônea existente entre os termos irradiação e radioatividade, frequentemente relacionados aos malefícios causados à saúde (França, 2000;Boaventura, 2004;Ornellas et al, 2006;Kuramoto, 2008).…”
Section: -Aceitação De Alimentos Irradiadosunclassified
See 1 more Smart Citation